Analysis of a wind farm with SCIG integrated into a high power system. Issue 3 (27th March 2020) - Malamov, Dian; Hadzhiev, Ivan; Zlatanova, Vasilina; Terzieva, Snejana; Georgiev, Aleksandar
Abstract : Purpose: The aim of this paper is a steady-state analysis of the basic electrical characteristics of a wind farm with squirrel-cage induction generators (SCIG), integrated into a high power system. The SCIG are connected to the system by means of a step-up substation 21/115 kV, realized by cable lines. Design/methodology/approach: The analyses have been done with the help of a computer model, developed in MATLAB/Simulink. Findings: Results have been obtained, concerning the influence of the SCIG on the active and reactive power, on the power factor and the voltage deviation in the cases of only one generator operating, all generators operating and disabled generators. Practical implications: The analysis has been carried out for an operating wind farm in the power system. The obtained results are applicable for optimizing and managing the modes of operation of the wind farm. Originality/value: A mathematical model for studying the electrical parameters of an SCIG integrated into a high power system has been described. A computer model in MATLAB/Simulink has been synthesized. Numerical results have been obtained, concerning the dependence of the active power, the reactive power, the power factor and the voltage deviation on the shaft torque of the wind farms with SCIG.